Academics and entrepreneurs : developing university-industry relations - Stankiewicz, Rikard (London : Frances Pinter, 1986)
Academia as a source of innovation and university-industry linkages have become a topic of increasing attention and even concern.
Includes bibliographical references: p. 122-155.
II 18/01/2019
Loans
Keywords: Academic-industrial collaboration; Research; Universities and colleges